Status, diversity and potential of indigenous and minor Alliums spp. - Kumar, Santosh; Nongthombama, Jotish; Dubey, R. K.; Chaudharya, K. P.; Devia, N. Leindah; Khangembama, Joshi Kumar (Indian Horticulture, 2020)
Allium which includes various historical vegetable crops besides onion and garlic like leek, scallion, shallot, wild garlic etc., is one of the largest genera with more than 700 species distributed throughout the world. Records of these plants have been found in the oldest known Indian Ayurvedic medical treatise, ‘Charaka Samhita’ as medicinal plant. Tracing its footprint, the first published monograph of Allium listed 24 species of the genus by Haller in the year 1745 that has eventually being increased to 750 species. Presently, Allium genus comprises more than 900 species including 15 subgenera and 57 sections; making it one of the largest monocotyledon genera distributed around the globe. Its region of diversity stretches from the Mediterranean basin to Central Asia and beyond. Important species of Allium includes onion and shallot (Allium cepa), garlic (Allium sativum), leek and elephant garlic (Allium ampeloprasum), Japanese bunching onion (Allium fistulosum), chives (Allium schoenoprasum), and garlic chives (Allium tuberosum). Further, many of its species are also grown as ornamentals, viz. Allium giganteum, Allium christophii, Allium karataviense, Allium aflatunense, Allium caeruleum, the nodding onion (Allium cernuum), the yellow flowered Allium moly, and the interspecific cultivar Globe master. A few Allium species are also noxious weeds in some parts of the world (e.g. Allium vineale and Allium triquetrum).